Corruption: Causes, consequences and eradication - Sharma, Subhash; Mishra, Devendra (2011)
Coruption has become so ingrained in the Indian psyche that often a large number of people casually remark that it is inevitable. It has come to hamper human flourishing in different ways. There has been a consistent decline in social and moral values in India and due to this decay a section of society is flourishing in collusion with the politicians, officialdom, contractor, suppliers, industrialists and traders. Corruption in the longer run affects the economy by distorting local, national and international trade in various ways, it ultimately makes democracy dysfunctional, because it devaluates the rule of law resulting into chaos and anarchy. Prevalence of corruption on a large scale leads to social, economic and politial exclusion. For eradication of corruption both values and institution equally matter because values serve as 'guiding stars' but are to be sustained by institutions to become durable and to serve as an example to others. - Reproduced.
Keywords: Corruption